IMPLEMENTASI ASAS KEBEBASAN BERKONTRAK PADA PERJANJIAN KERJA WAKTU TERTENTU DI PT.CIPTA NIAGA SEMESTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - ANDO GURNING; Maryati Bachtiar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
By normatif, rule about its valid condition of existing agreement in Section 1320 KUHPERDATA adopted fully by Section 52 sentence Code Number 13 Year 2003 about Labour. just Only is, because is fourth of its valid condition of existing agreement in Section 1320 KUHPERDATA have related to other civil principle of justices, hence solution about its valid condition of compilation of work agreement relate to KUHPERDATA and Code Number 13 Year 2003 about Labour.But, in the execution, work agreement is designedly made by including clause limiting labour rights.This Research type is classified in research of sosiologis yuridis, because direct writer perform a research at accurate place or location. This research is conducted in PT. Cipta Niaga Semesta branch Pekanbaru in Komplek Warehousing Of Avian Block of DD 02 Road;Street of Arengka II, while and population of sampel is to represent the overall of side related to problem of accurate in this research, source of data the used is primary data, data of sekunder data and of tertier, technique data collecting of research with observation, interview, bibliography study and enquette. Result of research found by that there is the parties rights and obligations imbalance him at PKWT between PT. Cipta Niaga Semesta Pekanbaru with employees. This prove that PT. Cipta Niaga Semesta Pekanbaru designedly impinge rule of ketenagakerjaan going into effect.From result of research can be concluded is. First, the parties rights and obligations at PKWT PT. Cipta Niaga Semesta uneven Pekanbaru. Side of PT. Cipta Niaga Semesta Pekanbaru only affirming its rights as employer to employees by giving obligation to employees through PKWT. Implementation Ground freedom contract at PKWT PT. Cipta Niaga Semesta Pekanbaru have been executed by both parties. But, in the execution there are deviation to applying at PKWT steming from freedom contract in making work agreement. Both, Resistance Implementation freedom ground contract at PKWT PT. Cipta Niaga Semesta Pekanbaru, namely its minim of knowledge of employees, side of PT. Cipta Niaga Semesta Pekanbaru is not consistent run order of ketenagakerjaan observation inexistence and of local institution. Third, Effort overcome freedom ground implementation resistance contract at PKWT PT. Cipta Niaga Semesta Pekanbaru is to improve knowledge of employees to rule of ketenagakerjaan, side of PT. Cipta Niaga Semesta Pekanbaru evaluate to repeat PKWT which they make for the labour of. The change to overcome some lacking of in items of PKWT at the same time alter some clausal weighing against labour and maximize observation of local institution like On Duty Labour Town of Pekanbaru.Keyword : Implementasi-Asas Freedom Of Contract-PT.Cipta Niaga Semesta branch Pekanbaru - Certain Work agreement Time.